2019
DOI: 10.3390/nano9060868
|View full text |Cite
|
Sign up to set email alerts
|

Optical Amplification in Hollow-Core Negative-Curvature Fibers Doped with Perovskite CsPbBr3 Nanocrystals

Abstract: We report a hollow-core negative-curvature fiber (HC-NCF) optical signal amplifier fabricated by the filling of the air microchannels of the fiber with all-inorganic CsPbBr3 perovskite nanocrystals (PNCs). The optimum fabrication conditions were found to enhance the optical gain, up to +3 dB in the best device. Experimental results were approximately reproduced by a gain assisted mechanism based on the nonlinear optical properties of the PNCs, indicating that signal regeneration can be achieved under low pump … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…However, in that particular case the measurements were performed in thin films. Recently, Suarez et al investigated the NLO properties of polycrystalline CsPbX 3 nanoparticles and films, and they have found the values of α 2 to be ∼10 –11 cm/W and n 2 to be 10 –13 cm 2 /W obtained with fs laser pulses excitation at a repetition rate of 1 kHz . Pramanik et al reported a 2PA cross section value of 2.1 × 10 6 GM from CsPbCl 3 QDs with 100 fs pulses at 80 MHz repetition rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in that particular case the measurements were performed in thin films. Recently, Suarez et al investigated the NLO properties of polycrystalline CsPbX 3 nanoparticles and films, and they have found the values of α 2 to be ∼10 –11 cm/W and n 2 to be 10 –13 cm 2 /W obtained with fs laser pulses excitation at a repetition rate of 1 kHz . Pramanik et al reported a 2PA cross section value of 2.1 × 10 6 GM from CsPbCl 3 QDs with 100 fs pulses at 80 MHz repetition rate.…”
mentioning
confidence: 99%
“…Recently, Suarez et al investigated the NLO properties of polycrystalline CsPbX 3 nanoparticles and films, and they have found the values of α 2 to be ∼10 −11 cm/W and n 2 to be 10 −13 cm 2 /W obtained with fs laser pulses excitation at a repetition rate of 1 kHz. 39 Pramanik et al 46 reported a 2PA cross section value of 2.1 × 10 6 GM from CsPbCl 3 QDs with 100 fs pulses at 80 MHz repetition rate. He et al 42 have demonstrated multiphoton absorption from colloidal Mn-doped CsPbCl 3 2D nanoplatelets and reported a 2PA cross section value of 3.6 × 10 5 GM.…”
mentioning
confidence: 99%
“…drawing tower must be modified to include application of cladding and buffer layers in practical fiber production. Successful fabrication of luminescent traditional fibers using a double-crucible approach [63], QD-doped hollow-core PCF [64] and QD-doped negativecurvature PCF [65], and many variations on the main theme have been reported in the scientific literature.…”
Section: Structured Fibers For Calorimetrymentioning
confidence: 99%
“…To overcome these problems, several attempts have been made to extend the functionality of optical fibers. For example, nanostructured elements have been arranged on the fiber facets to tailor the mode properties, and these have been employed in various applications, such as optical plasmonic sensors [4][5][6] , filters 7 , amplifiers 8 , and, optical tweezers 9 . In particular, optical lenses using plasmonic nanostructures have been actively investigated [10][11][12][13] .…”
Section: High Efficiency Dielectric Photonic Crystal Fiber Metalens Mmentioning
confidence: 99%